Thrombopoietin-receptor agonists for children with immune thrombocytopenia: a systematic review. (13th October 2017) - Zhang, Jiaxing; Liang, Yi; Ai, Yuan; Xie, Juan; Li, Youping; Zheng, Wenyi
ABSTRACT: Objective : We conducted a systematic review to assess the efficacy and safety of Thrombopoietin-receptor agonists (TPOras) for pediatric immune thrombocytopenia (ITP). Methods : We searched PubMed, Embase and Cochrane Library from their earliest records to January 2017. Randomized controlled trials (RCTs) were included. Primary outcomes were durable response and clinically significant bleeding. Secondary outcomes were overall response, overall bleeding events, the use of rescue medication and adverse events (AEs). Results : Five randomized RCTs (261participants) were included. Compared with placebo group, the proportion of patients achieving durable platelet response was significantly higher in Eltrombopag ( P = 0.0004) or Romiplostim ( P = 0.002) group, so was the overall response in Eltrombopag [ RR = 2.64, 95% CI (1.58, 4.44)] or Romiplostim [ RR = 5.05, 95% CI (2.21, 11.53)] group. Both clinically significant bleeding ( P = 0.04) and total bleeding ( P = 0.01) in Eltrombopag group were significantly less frequent than those in placebo group, while no significant difference between Romiplostim and placebo group. The proportion of patients receiving rescue medication, the incidence of overall AEs and serious AEs between TPO-receptor agonists and placebo group were not significantly different. Conclusion : TPOras might improve both durable and overall platelet response in pediatric ITP, compared with placebo.